Pengaruh Variasi Massa Adsorben Terhadap Kapasitas Adsorpsi Ion Logam Cu2+ Menggunakan Limbah Padat Tandan Kosong Sawit - Maysha Permata Sari; Elvie Yenie; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The adsorption process of artificial Cu2+ solutions was investigated using an adsorbent made from Empty Fruit Bunches . This study aims to calculate the adsorption capacity of Cu2+ metal ions by varying the mass of the adsorbent from waste from carbonized Oil Palm Empty Fruit Bunches at 3500C. The mass of the adsorbent used was 2, 4, 6, 8 and 10 grams. The results showed that the best adsorption capacity occurred at a mass of 2 grams, which was 3.882 mg/g. Keywords: Cu2+, TKS, Adsorption, Capacity Adsorption.